2006
DOI: 10.1103/physrevlett.97.090401
|View full text |Cite
|
Sign up to set email alerts
|

Bosonic Molecules in Rotating Traps

Abstract: We present a variational many-body wave function for repelling bosons in rotating traps, focusing on rotational frequencies that do not lead to restriction to the lowest Landau level. This wave function incorporates correlations beyond the Gross-Pitaevskii (GP) mean field approximation, and it describes rotating boson molecules (RBMs) made of localized bosons that form polygonal-ring-like crystalline patterns in their intrinsic frame of reference. The RBMs exhibit characteristic periodic dependencies of the gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 21 publications
5
36
0
Order By: Relevance
“…Motivated by the discovery in the case of electrons of REMs at high B (and from the fact that Wigner molecules form also at zero magnetic field [28,29,30,31,32,33]) some theoretical studies have most recently shown that analogous molecular patterns of localized bosons do form in the case of a small number of particles inside a static or rotating harmonic trap [34,35,36,37,38]. In analogy with the electron case, the bosonic molecular structures can be referred to [36] as rotating boson molecules (RBMs); a description of RBMs via a variational wave function [39] built from symmetry-breaking displaced Gaussian orbitals with subsequent restoration of the rotational symmetry was presented in Refs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Motivated by the discovery in the case of electrons of REMs at high B (and from the fact that Wigner molecules form also at zero magnetic field [28,29,30,31,32,33]) some theoretical studies have most recently shown that analogous molecular patterns of localized bosons do form in the case of a small number of particles inside a static or rotating harmonic trap [34,35,36,37,38]. In analogy with the electron case, the bosonic molecular structures can be referred to [36] as rotating boson molecules (RBMs); a description of RBMs via a variational wave function [39] built from symmetry-breaking displaced Gaussian orbitals with subsequent restoration of the rotational symmetry was presented in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The quantity P (r, r 0 ) is proportional to the probability of finding a boson at r given that there is another boson at the observation point r 0 , and it is often referred to as the conditional probability distribution [22,23,30,33,34,36] (CPD). A main finding of our study is that consideration solely of the CPDs is not sufficient for the boson case at high fractional fillings ν ≥ 1/2; in this case, one needs to calculate even higher-order correlation functions, e.g., the full N -point correlation function P (r; r 1 , r 2 , ..., r N −1 ) [see Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rotational properties of BEC and creation of vortices in a harmonic trap have been analyzed mostly by the mean-field approach like Gross-Pitaevskii scheme as in Refs. [22][23][24][25][26][27] or beyond the mean-field approximation [23,[28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Many excellent experimental and theoretical papers focus on the formation and melt of vortex lattice [5], many-body energy spectrum [6,7], its analogy to quantum Hall effect of electrons in a magnetic field [8][9][10][11][12][13], particle localization and vortex localization [14][15][16][17], the comparison between the results of exact quantum numerical solution and mean-field theory [18] and so on. However, the entanglement in this system has not been investigated as extensively as in other condensed matter systems, for example in spin chain systems.…”
Section: Introductionmentioning
confidence: 99%